Palynology of Philippine Amorphophallus Blume ex Decne. (Araceae) and its taxonomic implications - NORILYN F. FONTARUM-BULAWIN; MARIA MELANIE P. MEDECILO-GUIANG; MICHAEL A. CALARAMO; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2023)
Abstract. Fontarum-Bulawin NF, Medecilo-Guiang MMP, Calaramo MA, Alejandro GJD. 2023. Palynology of Philippine Amorphophallus Blume ex Decne. (Araceae) and its taxonomic implications. Biodiversitas 24: 4095-4109. Amorphophallus is one of the genera of Araceae with diverse pollen characters. This study aimed to investigate the pollen morphological characters of Amorphophallus in the Philippines for inferring taxonomical relationships. Light microscopy (LM) and scanning electron microscopy (SEM) were employed to investigate pollen morphology of 14 accessions of Amorphophallus. Both acetolyzed and unacetolyzed pollens were studied to compare the outward aspect of pollens and the pollen characters were subjected to cluster analysis. Results revealed that pollen grains were mostly spheroidal, prolate-spheroidal, and subspheroidal in shape. The pollen sizes vary from 3.0 to 50 µm and exhibit very small to medium sizes. The ornamentations of unacetolyzed pollens were psilate and striate, whereas ornamentations in acetolyzed pollens are varied from psilate, rugulate, rugulate hamulate, reticulate, scabrate, striateto verrucate ornamentations. All pollens were inaperturate and monad. Cluster analysis using Euclidean generated 2 major clusters, namely Cluster I consists of Amorphophallus adamsensis Magtoto, Mones, Ballada, Austria, R.M.Dizon, Alangui, Regina, Amorphophallus sp.3 (Samar), Amorphophallus yaoi A.Galloway, Hett. & Medecilo, Amorphophallus flammeus Calaramo, Batuyong, Bulawin & Alejandro, Amorphophallus urceolatus Hett. et al. (Ilocos), Amorphophallus rayongii Hett. & Medecilo, Amorphophallus sp.2 (Romblon), and Amorphophallus urceolatus Hett., A.Galloway & Medecilo (Cavite); and cluster 2 consists of Amorphophallus paeoniifolius (Dennst.) Nicolson, Amorphophallus fontarumii Bulawin, Medecilo & Alejandro, Amorphophallus rostratus Hett., Amorphophallus longispathaceus Engl.& Gehrm., and Amorphophallus sp.1 Based on this study, pollen shape, size, and ornamentation can be used as supplemental characters for the taxonomic identification of Amorphophallus in the Philippines.